Exploration of Pharmacological Mechanism of Cinnamomum tamala Essential Oil in Treating Inflammation based on Network Pharmacology, Molecular Modelling, and Experimental Validation - Mohanty, Debajani; Padhee, Sucheesmita; Jena, Sudipta; Sahoo, Ambika; Panda, Pratap Chandra; Nayak, Sanghamitra; Ray, Asit (Current Pharmaceutical Design, 2024)
Background Cinnamomum tamala (Buch.-Ham.) T.Nees & Eberm., also known as Indian bay leaf, holds a distinctive position in complementary and alternative medicinal systems due to its anti-inflammatory properties. However, the active constituents and key molecular targets by which C. tamala essential oil (CTEO) exerts its anti-inflammatory action remain unclear. Objective The present study used network pharmacology and experimental validation to investigate the mechanism of CTEO in the treatment of inflammation. Methods GC-MS analysis was used to identify the constituents of CTEO. The key constituents and core targets of CTEO against inflammation were obtained by network pharmacology. The binding mechanism between the active compounds and inflammatory genes was ascertained by molecular docking and molecular dynamics simulation analysis. The pharmacological mechanism predicted by network pharmacology was verified in lipopolysaccharide-stimulated murine macrophage (RAW 264.7) cell lines. Results Forty-nine constituents were identified by GC-MS analysis, with 44 constituents being drug-like candidates. A total of 549 compounds and 213 inflammation-related genes were obtained, revealing 68 overlapping genes between them. Compound target network analysis revealed cinnamaldehyde as the core bioactive compound with the highest degree score. PPI network analysis demonstrated Il-1β, TNF-α, IL8, IL6 and TLR4 as key hub anti-inflammatory targets. KEGG enrichment analysis revealed a Toll-like receptor signalling pathway as the principally regulated pathway associated with inflammation. A molecular docking study showed that cinnamaldehyde strongly interacted with the Il-1β, TNF-α and TLR-4 proteins. Molecular dynamics simulations and MMPBSA analysis revealed that these complexes are stable without much deviation and have better free energy values. In cellular experiments, CTEO showed no cytotoxic effects on RAW 264.7 murine macrophages. The cells treated with LPS exhibited significant reductions in NO, PGE2, IL-6, TNF-α, and IL-1β levels following treatment with CTEO. Additionally, CTEO treatment reduced the ROS levels and increased the antioxidant enzymes such as SOD, GSH, GPx and CAT. Immunofluorescence analysis revealed that CTEO inhibited LPS-stimulated NF-κB nuclear translocation. The mRNA expression of TLR4, MyD88 and TRAF6 in the CTEO group decreased significantly compared to the LPS-treated group. Conclusion The current findings suggest that CTEO attenuates inflammation by regulating TLR4/MyD88/NF-κB signalling pathway.
Keywords: murine macrophages